Gender Differences Related to Spirituality, Coping Skills and Risk Factors of Suicide Attempt: A Cross-Sectional Study of French Adolescent Inpatients - Mirkovic, Bojan; Belloncle, Vincent; Pellerin, Hugues; Guilé, Jean-Marc; Gérardin, Priscille (Frontiers in Psychiatry, 2021)
Background: Suicide attempts in adolescence represent a major public health concern, since these behaviours are associated with psychosocial burden and an increased risk of suicide. This cross-sectional study aimed to explore possible gender differences related to protective and risk factors in adolescents who have attempted suicide. Methods: Participants were French adolescents hospitalized for attempt suicide in five French paediatric departments. The participants were evaluated on 12 instruments measuring individual risk and protective factors. Results: Our sample included 320 adolescents aged 13 to 17 years (M = 14.43, SD = 1.29), of whom 82% were female and 35% were repeat attempters. Boys had greater difficulties at school and used more lethal means such as strangulation. We failed to find any differences between the two groups as regards the main Axis I psychiatric diagnoses. Boys tend to use more non-productive coping skills such as tension reduction or wishful thinking and girls use more reference to other strategies such as seeking social support. Although spirituality scores were low overall sample, they were significantly higher among girls. Conclusions: In the end, we find little difference between the two groups in terms of risk factors. However, we have shown gender differences in spirituality and some coping strategies. These results should be taken into consideration when designing suicide prevention programs.